The making of the Tuoba Northern Wei: constructing material cultural expressions in the Northern Wei Pingcheng Period (398-494 CE) - Tseng, C (2012)
The Tuoba’s success in the making of the Northern Wei as a conquest dynasty in fifth century northern China will be argued in this thesis as a result of their ability to cross between the traditions and practices of the Chinese sphere and those of the Eurasian steppe, through the construction of a "dual presence" in the Pingcheng period (398-494 CE). A negotiation of material culture in this formative phase of state-building allowed for new notions of kingship, dynastic identity, and representations of daily life to be (re)created. This was manifested separately through the application of mountain-side stone sculptures, tomb repertoires, as well as the conception of Pingcheng as a capital city. The material cultural expressions explored in this thesis reflect significant changes in the socio-cultural atmosphere at this point in history. In effect, these ritual, funerary, and commemorative discourses wove together to create new notions of "Chineseness" in fifth century northern China. In the following discussion, we will come to recognize the Tuoba’s maintenance of a "dual presence", not only as "Son of Heaven" to the conquered subjects, but also carrying over practices that befit a Khagan in the Central Asian tradition, as an act of ingenuity.